Poskolonial dan Developmentalisme: Telaah Kritis (Department of International Relations, Universitas Brawijaya, 2022)
ABSTRACTThe relation between postcolonial theory and developmentalism does not run linearly, but there is a contradictory dialogue space. This article aims to explain the rejection of postcolonial theory to the paradigm and practice of developmentalism through an evaluation of debates in the philosophical realm. This article answers the debates in postcolonial studies, including the theorizing of political economy, development, and international politics. This rejection stems from the fact that developmentalism is considered a new form of colonization in the economic aspect, extending to social, political, and cultural aspects. The results show that the opposition of postcolonial theory to developmentalism can be explained through four discussions as the unit of analysis, which consists of the international trade system, capital distribution schemes, the role of global institutions, and the existence of the state and its people.ABSTRAKRelasi di antara teori poskolonial dan developmentalisme tidak berjalan secara linear, melainkan terdapat ruang dialog di dalamnya yang saling bertentangan. Artikel ini bertujuan untuk menjelaskan penolakan teori poskolonial terhadap paradigma dan praktik developmentalisme melalui evaluasi perdebatan dalam ranah filosofis. Artikel ini menjawab perdebatan dalam studi poskolonial yang mencakup tentang teorisasi ekonomi politik, pembangunan, dan politik internasional. Penolakan tersebut bersumber dari fakta bahwa developmentalisme dianggap sebagai bentuk kolonisasi baru dalam aspek ekonomi yang kemudian meluas pada aspek sosial, politik, dan budaya. Hasil menunjukkan bahwa pertentangan teori poskolonial terhadap developmentalisme dapat dijelaskan melalui empat sektor pembahasan sebagai unit analisis, yaitu terdiri dari sistem perdagangan internasional, skema pendistribusi modal, peranan institusi global, serta keberadaan negara dan masyarakatnya.